2019
DOI: 10.1093/toxsci/kfz222
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Serum Biomarkers to Distinguish Hazardous and Benign Aminotransferase Elevations

Abstract: The standard circulating biomarker of liver injury in both clinical settings and drug safety testing is alanine aminotransferase (ALT). However, ALT elevations sometimes lack specificity for tissue damage. To identify novel serum biomarkers with greater specificity for injury, we combined unique animal models with untargeted proteomics, followed by confirmation with immunoblotting. Using proteomics, we identified 109 proteins in serum from mice with acetaminophen (APAP)-induced liver injury that were not detec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 42 publications
0
18
0
Order By: Relevance
“…MS data will be acquired using the FTMS analyzer in profile mode at a resolution of 240,000 over a range of 375 to 1500 m/z. Following HCD activation, MS/MS data will be acquired using the ion trap analyzer in centroid mode and normal mass range with precursor mass-dependent normalized collision energy between 28.0 and 31.0 [ 48 , 49 ].…”
Section: Methodsmentioning
confidence: 99%
“…MS data will be acquired using the FTMS analyzer in profile mode at a resolution of 240,000 over a range of 375 to 1500 m/z. Following HCD activation, MS/MS data will be acquired using the ion trap analyzer in centroid mode and normal mass range with precursor mass-dependent normalized collision energy between 28.0 and 31.0 [ 48 , 49 ].…”
Section: Methodsmentioning
confidence: 99%
“…34 In another aspect, changes in ALDH1A1 expression appear to be part of the early acutephase hepatic inflammatory response 35 and ALDH1A1 is a promising biomarker for liver injury. 36 Moreover, the ALDH1A1*2 allele has an increased risk of liver toxicity, compared with patients with wild-type alleles when treated with a high-dose chemotherapy combination of cyclophosphamide, thiotepa, and carboplatin. 37 Given the above evidence, it would be of great value to investigate the relationship between ALDH1A1 and liver injury from anti-TB treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Rebollido‐Rios et al found that nonsmall cell lung cancers with increased expression of ALDH1A1, ALDH1A3, or ALDH3A1 may be targeted by strategies involving inhibitors of these isoenzymes as monotherapy or in combination with chemotherapy to overcome patient‐specific drug resistance 34 . In another aspect, changes in ALDH1A1 expression appear to be part of the early acute‐phase hepatic inflammatory response 35 and ALDH1A1 is a promising biomarker for liver injury 36 . Moreover, the ALDH1A1*2 allele has an increased risk of liver toxicity, compared with patients with wild‐type alleles when treated with a high‐dose chemotherapy combination of cyclophosphamide, thiotepa, and carboplatin 37 .…”
Section: Introductionmentioning
confidence: 99%
“…The bardoxolone methyl experience highlights the urgent need for better DILI biomarkers and some promising new biomarkers have been proposed. 8,9 The key limiting factor in validation of new DILI biomarkers is the lack of serial serum samples prospectively collected and archived from clinical trials that have demonstrated varying degrees of liver safety. This will require standardized sample collection, storage, and retrieval of relevant phenotypic data.…”
mentioning
confidence: 99%
“…However, the effects are modest and not consistent with the substantial ALT elevations observed in the clinical trials and seem unlikely to convince regulators of the safety of this drug candidate. The bardoxolone methyl experience highlights the urgent need for better DILI biomarkers and some promising new biomarkers have been proposed 8,9 . The key limiting factor in validation of new DILI biomarkers is the lack of serial serum samples prospectively collected and archived from clinical trials that have demonstrated varying degrees of liver safety.…”
mentioning
confidence: 99%